(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The trajectory of English poetry from the medieval period to the Romantic age demonstrates profound transformations in style, form, and thematic focus. Beginning with Geoffrey Chaucer, whose Canterbury Tales exemplifies early narrative ingenuity and lyrical experimentation, English poetry laid the groundwork for exploring human nature, social dynamics, and ethical reflection. During the Renaissance, poets such as Edmund Spenser and William Shakespeare expanded formal techniques, rhyme schemes, and classical influences, enriching poetic expression. The Neoclassical period, represented by figures like Alexander Pope and John Dryden, emphasized rationality, structure, and societal ideals. In contrast, the Romantic era heralded a focus on personal emotion, imagination, and a profound connection with nature, with poets such as William Wordsworth, Samuel Taylor Coleridge, and Percy Bysshe Shelley exemplifying this shift. This study examines how historical, cultural, and intellectual developments shaped the evolution of English poetry, demonstrating the interplay between societal change and artistic innovation that underpins the enduring richness of the English literary tradition.